Spect scintigraphic TC-99m HMPAO appearance in pre- and post electroconvusive therapy (ECT) in patients with major depression - Vangu, Mboyo-Di-Tamba Heb'En Willy (My University, 2014)
The attention recently gained by functional brain imaging research in affective disorders is considerable. Decreases in regional cerebral blood flow in depressed patients have been reported in the limbic and paralimbic areas by tomographic imaging techniques (Ito et al, 1996; Mayberg et al, 1994). Studies examining the long term effects of electroconvulsive therapy (ECT) on the cerebral perfusion demonstrate contrasting results in both the responders and non responders (Silfverskiold et al, 1986; Nobler et al, 1994). The aim ofthis study was to observe regional cerebral blood flow (rCBF) changes in patients with major depression while using brain SPECT imaging before and after a course of ECT. 15 patients with major depression diagnosed according to DSM-IV criteria were investigated in this study., They were 11 females and 4 males who did not respond to pharmaceutical treatment. Their mean age was 36.9 + 11.9 and except for two who refused ECT after the pretreatment imaging, all the others scored at least 17 on the Hamilton Rating Scale for Depression (HAM-D), mean 25.8 ± 4.7. The data analysis consisted of visual assessment and semiquantitetive evaluation of 99mTc-HMPAO uptake ratios measured between cerebral regions of interest and the cerebellum. The results in the group of responders showed obvious improvement on visual assessment and unchanged patterns in non responders. Two of the 15 patients showed signs of post traumatic stress disorder (PTSD) after ECT and demonstrated peculiar patterns regarding their response to therapy. When patients were considered as a whole, significant changes on the semiquantitative evaluation were noted in the anterior cingulate gyrus and the left frontal area, in keeping with available literature. When patients were separated in groups of responders versus non responders however, no significant change was noted between the pre and post ECT studies.